2019
DOI: 10.1371/journal.pone.0211538
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Natural Killer cell NKG2D and CD226 anti-tumour cascades by platelet cloaked cancer cells: Implications for the metastatic cascade

Abstract: Tumour cell immune evasion is a principal hallmark of successful metastasis. Tumour cells in the vasculature adopt a platelet cloak that efficiently suppresses the innate immune system by directly inhibiting Natural Killer (NK) cells, which normally function to neutralise spreading cancers. Here we describe two novel mechanisms of tumour cell evasion of NK cell anti-tumour functions. The first, an ‘immune decoy’ mechanism in which platelets induce the release of soluble NKG2D ligands from the tumour cell to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 28 publications
3
48
0
Order By: Relevance
“…Assessment of degranulation responses with the GM NK-92 cell-based screening platform showed that NKG2D + GM NK-92 cells had enhanced degranulation against majority of the cell lines except for SH-SY5Y ( Figure 7A). In line with this observation, previous studies and the human protein atlas database demonstrated moderate/high expression of at least one NKG2D ligand in all cell lines used except in the neuroblastoma cell line SH-SY5Y (35)(36)(37)(38)(39)(40)(41). Importantly, identification of differential receptor-mediated responses against tested cells lines such as DM6, THP-1, and ARH-77 cell lines, validates the functionality of each receptor introduced to NK-92 cells, and further demonstrates the applicability of the NK cell-based screening platform for the identification of tumor type-and most importantly patient-specific targetable NK cell receptor/ligand interactions (Figure 7A).…”
Section: Dnam-1 + and Nkg2d + Gm Nk-92 Cells Provide A Novel Approachsupporting
confidence: 76%
“…Assessment of degranulation responses with the GM NK-92 cell-based screening platform showed that NKG2D + GM NK-92 cells had enhanced degranulation against majority of the cell lines except for SH-SY5Y ( Figure 7A). In line with this observation, previous studies and the human protein atlas database demonstrated moderate/high expression of at least one NKG2D ligand in all cell lines used except in the neuroblastoma cell line SH-SY5Y (35)(36)(37)(38)(39)(40)(41). Importantly, identification of differential receptor-mediated responses against tested cells lines such as DM6, THP-1, and ARH-77 cell lines, validates the functionality of each receptor introduced to NK-92 cells, and further demonstrates the applicability of the NK cell-based screening platform for the identification of tumor type-and most importantly patient-specific targetable NK cell receptor/ligand interactions (Figure 7A).…”
Section: Dnam-1 + and Nkg2d + Gm Nk-92 Cells Provide A Novel Approachsupporting
confidence: 76%
“…This was mirrored by enhanced detection of soluble NKG2DL, pointing to increased shedding of the surface expressed ligands. These observations were also confirmed by another group evaluating different tumor entities (121). Alike Cluxton and coworkers, we did not find enhanced mRNAlevels of tumor-ADAM10 (or ADAM17) upon platelet coating.…”
Section: Non-canonical Shedding Activity Of Padam10supporting
confidence: 90%
“…Additionally, coating of tumor cells with platelets allows transferring their major histocompatibility complex (MHC) class I to tumor cells, thereby giving these cells a false "pseudonormal" exterior, and allowing escape from immunosurveillence by natural killer cells [149]. TGFβ released by platelets also downregulates the NK receptor NKG2D on tumor cells, further shielding them from immunosurveillence [150,151]. Lastly, extravasation of the tumor cells from the blood stream is facilitated by platelets, and appears to require binding of platelets to Integrin ανβ3 expressed on tumor cells [152].…”
Section: Platelets Drive Tumor Growth Angiogenesis and Metastasis Imentioning
confidence: 99%